SOSIALISASI BAHAYA ROKOKGUNA MENINGKATKANKESADARAN MASYRARAKAT AKANBESARNYA DAMPAK BURUK ROKOK BAGI KESEHATAN - Awaluddin Nurmiyanto (Asian Journal of Innovation and Entrepreneurship, 2013)
Smoking is an activity that is now being in gandrungi by our youth. Once upon atime smoking is simply being part of the lives of older people-people. But now thesmoke has penetrated into the lives of school children. Behind the pleasure felt by thesmoker a hazard which is deadly to himself and his future life. This is what wanted to beprevented through socialization. Because when the smoke has become a commonlypracticed by society in general, the dangers of smoking will also staking its future. Thefuture smokers will be gloomy, look at when they are addicted to consuming a cigarette,If it is fatal, then they will do everything they can to be able to enjoy a cigarette.Diseases that arise will depend on the levels of harmful substances contained, the periodof smoking habits, and how to smoke cigarettes. The younger a person starts smoking,the greater the risk that person got the disease while older.